Recovery Of Carotenes And Tocopherols From Palm Oil Mill Effluent Via Extraction And Chromatography - Chan, Choi Yee (2010)
Carotenes and tocopherols provide plenty of health benefits and are important in food, cosmetic and pharmaceutical industries. Due to the increasing demand for these natural products, this study aims to investigate the feasibility of recovering carotenes and tocopherols from agricultural wastewater abundantly available in Malaysia, which is the palm oil mill effluent (POME). Solvent extraction was used to retrieve oil from POME whereas adsorption chromatography approach was employed to recover carotenes and tocopherols from the extracted oil.